The Urgency of Restorative Justice in Renewing Criminal Law - Henny Saida Flora; Maidin Gultom; Parulian Samosir; Khomaini Khomaini; Bobur Sobirov (Unissula, 2024)
This change in the concept of punishment is partly due to the consequences of imprisonment having greater negative effects and not proving its success in reducing crime rates. The purpose of this writing is to analyze the retributive justice paradigm in current criminal law enforcement, and to analyze the urgency of restorative justice in criminal law reform in Indonesia. The research uses a normative juridical approach and the specifications of this research use descriptive analysis methods. The results of this research are that the punishment system through imprisonment makes a prisoner isolated from society and family, so that psychologically the prisoner can experience stress and decline in mental health. The concept of restorative justice offers a recovery process that involves the perpetrator and victim or the victim's family directly in solving the problem. The application of restorative justice returns the conflict to the parties in order to emphasize human rights and the need to restore the impact of social injustice in a simple way, still providing the perpetrators with justice rather than formal (legal) justice where victims do not get justice. Restorative justice also seeks to restore security, personal respect and dignity to the victim.